A Semiotic Analysis of the Characteristics of Communicational Thinking in Collaborative Problem Solving - Su Min Kim; Sun Hee Kim (Korea Society of Educational Studies in Mathematics, 2020)
The purpose of this study was to analyze the characteristics of communicational thinking in successful collaborative problem solving. In collaborative problem solving communication, the sender and receiver infer meaning to all mathematical objects and interpret them. From the semiotic perspective, this study reached the following results by analyzing the interpretants formed from the objects. First, in the early stages of problem solving, immediate interpretant were formed from the communicational thinking of students' guesses, hypotheses, and perceptions, revealing the purpose-oriented characteristics of communicational thinking. Second, many dynamic interpretants were made in the communicational thinking, allowing the sign to perform practically. Third, the final interpretant obtained as a result of the students' communicational thinking confirmed that the problem solving result has a universal character that can be recognized by anyone. Based on these findings, it is suggested that teachers must design tasks that allow them to use a variety of mathematical approaches on their own. And it is suggested that affective as well as cognitive domain should be achieved and that studies to examine students' thinking process by applying semiotics should be activated.